2022
DOI: 10.1111/jocs.16396
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of cardiac surgery in nonagenarians

Abstract: Background While advanced age can be considered by some a contraindication to open‐heart surgery, there is a paucity of data regarding outcomes of cardiac surgery in nonagenarians. We, therefore, sought to investigate the outcomes of nonagenarians undergoing cardiac surgery. Methods A retrospective review of our institutional Society of Thoracic Surgeons database between 1993 and 2019 was performed. Among a total of 32,421 patients who underwent open‐heart surgery, 134 patients (0.4%) were nonagenarians (50.7%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…On extended follow-up out to 15 years there was a significant difference with greater mortality in nonagenarians, which is to be expected due to lower baseline life expectancy. 63 These data again present morbidity and mortality in nonagenarians undergoing cardiac surgery that is higher than in a younger cohort, but within acceptable ranges. In this patient population, assessment of baseline functional status and postoperative expectations is of paramount importance.…”
Section: Management Of Aortic Valvular Disease In the Elderlymentioning
confidence: 70%
“…On extended follow-up out to 15 years there was a significant difference with greater mortality in nonagenarians, which is to be expected due to lower baseline life expectancy. 63 These data again present morbidity and mortality in nonagenarians undergoing cardiac surgery that is higher than in a younger cohort, but within acceptable ranges. In this patient population, assessment of baseline functional status and postoperative expectations is of paramount importance.…”
Section: Management Of Aortic Valvular Disease In the Elderlymentioning
confidence: 70%
“…As Transcatheter Aortic Valve Replacement (TAVR) has emerged in the recent era between 2011 and 2019, the incidence of Surgical Aortic Valve Replacement (SAVR) in the Mayo group of nonagenarians and octogenarians declined to 0.3%, with all of those SAVRs done in 2011. This brought operative mortality of SAVR down to 4% from 1993 to 2011, with comparable TAVR mortality of 1% from 2011 to 2019 in the reported group 20. The STS‐PROM risk scores underrepresented the 30‐day mortality in nonagenarians in this patient cohort.…”
Section: Introductionmentioning
confidence: 69%
“…Presently, studies analyzing the outcomes of these patients have not been sufficiently reported. In fact, most studies in the literature on this topic have a very limited number of patients [ 2 , 3 , 4 , 5 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]: from just over 10 patients [ 3 , 15 ] to a maximum of 49 [ 11 ]. Two articles present slightly more than 100 patients [ 4 , 5 ]; however, in these papers, nonagenarian patients are drawn from large national databases consisting of thousands of patients.…”
Section: Commentsmentioning
confidence: 99%
“…In fact, most studies in the literature on this topic have a very limited number of patients [ 2 , 3 , 4 , 5 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]: from just over 10 patients [ 3 , 15 ] to a maximum of 49 [ 11 ]. Two articles present slightly more than 100 patients [ 4 , 5 ]; however, in these papers, nonagenarian patients are drawn from large national databases consisting of thousands of patients. Thus, our study, with more than 200 patients aged over 90 enlisted, currently represents the largest case study from a single hospital group.…”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation